Novel candidate plasma proteins for the pathogenesis and treatment of atopic dermatitis revealed by proteome-wide association study - Chen Luo; YaJing Zhang; QiFan Feng; KaiXin Yao; LeiLei Zheng; Ye Yang; WenXin Zheng; Feng Li; YongQiang Lv; Yue Cai (Scientific Reports)
Abstract Atopic dermatitis (AD) is an immune-related skin disease with a genetic background. Numerous loci have been identified associated with AD to better comprehend its complicated genetic mechanisms by genome‑wide association studies (GWASs). However, current studies reveal the underlying mechanisms of these loci in the pathogenesis of AD inadequately. Therefore, we integrated the GWAS statistics of AD with plasma proteins to explore candidate proteins correlated with the pathogenesis of AD based on protein-centered omics studies. Herein, we adopted the updated AD GWAS statistics (N = 864,982) and the dataset of plasma protein quantitative trait loci (pQTLs), comprising 1,348 proteins from individuals of European descent. We first conducted the AD-related proteome-wide association studies (PWASs) (N = 7,213) by integrating pQTLs with the AD GWAS statistics and identified twenty-six significant plasma proteins by PWAS (FDR < 0.05). Then, the potential causal proteins of AD were identified via Mendelian randomization (MR), and seventeen causal proteins of AD were discovered afterward. Following this, Bayesian colocalization analysis was then utilized to explore proteins sharing the same causal variants. Five causal proteins strongly associated with the pathogenesis of AD were eventually pinpointed. Finally, we discovered drugs that could be repurposed for AD with the plasma proteins that might contribute to the pathogenesis of AD in the Drug Gene Interaction Database.